A label free electrochemical nanobiosensor study - Zhang, Juankun; Dong, Shanmu; Lu, Jinhui; Turner, Anthony P. F.; Fan, Qingjie; Jia, Shiru; Yang, Hongjiang; Qiao, Changsheng; Zhou, Hao; He, Guowei (Taylor & Francis, 2009)
Nano-porous silicon (PS) is an attractive material for incorporation into biosensors, because it has a large surface area combined with the ability to generate both optical and electrical signals. In this paper, we describe a label-free nanobiosensor for bovine serum albumin (BSA). Nano-porous silicon produced in our laboratory was functionalized prior to immobilization of anti-BSA antibody on the surface. Reaction with BSA in phosphate buffered saline (PBS) buffer resulted in an impedance change which was inversely proportional to the concentration of the analyte. The system PBS buffer/antigen-antibody/PS constitutes an electrolyte-insulator-semiconductor (EIS) structure, thus furnishing an impedance EIS nanobiosensor. The linear range of the sensor was 0-0.27 mg mL-1 and the sensitivity was less than 10 µg mL-1.
Keywords: Electrolyte-insulator-semiconductor; impedance; nano-porous silicon; nanobiosensor